CONTAMINATION OF SOIL WITH EGGS OF TOXOCARA CANIS IN PUBLIC PARKS OF SANTIAGO DE SURCO, LIMA, PERU, 2007-2008 - Iannacone, josé (2012)
Soil contaminated with helminth parasites of animals can pose risks of zoonoses to humans. It is important to determine the transmission dynamics of embryonated eggs of Toxocara canis (Werner, 1782). The aim of this study was to evaluate soil contamination by T. canis eggs in public parks in the district of Santiago de Surco, Lima, Peru in 2007 and 2008. The study was descriptive, longitudinal and comparative. Soil samples were evaluated in November-2007 (spring, n = 39), June-2008 (autumn, n = 37) and November-2008 (spring, n = 41); a total of 117 samples of soil (n = 84) and grass (n = 33) from 51 public parks representing the district of Santiago de Surco, Lima, Peru. At each site we measured the area of the park, collecting between 1 to 1.5 kg of soil sample into five equidistant points (four laterals and one central) at a depth of 5 cm. The samples were stored at room temperature for parasitological examination for 2-3 days and 7 days for physicochemical characterization: pH and particle size (texture). The samples were analyzed using the method with supersaturated solution of sodium chloride (NaCl) (Willis-Molloy) for egg flotation. Eggs of T. canis were found in 69.2% (81/117) of the samples. 73.8% (62/84) of soil samples and 57.6% (19/33) of the grass samples were positive for T. canis. The presence of T. canis showed significant differences and the following sequence according to sampling: Spring 2007 (85.4%), spring 2008 (82.1%), autumn 2008 (37.8%). No relationship was found between pH and particle size in the presence of T. canis. No differences were observed between the presence of eggs in the grass and soil of public parks studied. An analysis of 40 references from 11 Latin American countries showed that the average prevalence of soil with eggs of Toxocara sp. was 46.9% ± 23.2% and the average number of samples examined was 144 ± 202. Public parks are areas of risk of zoonosis by nematoda ascaroidea.